A Comparison of Barbed Sutures and Standard Sutures with regard to Wound Cosmesis in Panniculectomy and Reduction Mammoplasty Patients. (29th November 2016) - Aliano, Kristen; Trostler, Michael; Fromm, Indira Michelle; Dagum, Alexander; Khan, Sami; Bui, Duc
Abstract : Cosmesis is a vital concern for patients undergoing plastic and reconstructive surgery. Many variations in wound closure are employed when attempting to minimize a surgical scar's appearance. Barbed sutures are one potential method of achieving improved wound cosmesis and are more common in recent years. To determine if barbed sutures differ from nonbarbed in wound cosmesis, we conducted a single-blinded, randomized, controlled trial of 18 patients undergoing bilateral reduction mammoplasty or panniculectomy. Patients were their own controls, receiving barbed sutures on one side and standard sutures on the contralateral side. Surgical scars were evaluated postoperatively by patient preference self-assessment and an observer. Ten patients were evaluated at 3 months postoperatively, yielding a mean Stony Brook Scar Evaluation Scale (SBSES) rating of 4.4 for barbed suture and 3.5 for regular suture (p = 0.15 ). At 6 months, 8 patients performed self-assessment to determine their preference; 4 preferred the barbed sutures, 1 preferred the regular sutures, and 3 had no preference. Further research with larger sample sizes is needed to determine if barbed sutures convey any advantage over standard sutures in wound healing. However, our results suggest that barbed sutures are a reasonable alternative to standard sutures particularly with regard to wound cosmesis.